2021
DOI: 10.3390/ijerph18052353
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Indicator Bacteria Data to Characterize Drinking Water Quality in Low-Resource Settings: Summary of Current Practices and Recommendations for Improving Validity

Abstract: Fecal indicator bacteria (FIB) values are widely used to assess microbial contamination in drinking water and to advance the modeling of infectious disease risks. The membrane filtration (MF) testing technique for FIB is widely adapted for use in low- and middle-income countries (LMICs). We conducted a systematic literature review on the use of MF-based FIB data in LMICs and summarized statistical methods from 172 articles. We then applied the commonly used statistical methods from the review on publicly avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Additionally, these estimates represented an average over time, which may have attenuated the apparent associations between measures. Previous work has suggested that incomplete and erroneous reporting in water quality can produce misleading results 20 , which would then propagate to modeled estimates. Finally, our analysis measures cholera risk only through mean annual incidence, but metrics like outbreak size and frequency 21 may better capture the relationship between water and sanitation access and cholera transmission efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these estimates represented an average over time, which may have attenuated the apparent associations between measures. Previous work has suggested that incomplete and erroneous reporting in water quality can produce misleading results 20 , which would then propagate to modeled estimates. Finally, our analysis measures cholera risk only through mean annual incidence, but metrics like outbreak size and frequency 21 may better capture the relationship between water and sanitation access and cholera transmission efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these estimates represented an average over time, which may have attenuated the apparent associations between measures. Previous work has suggested that incomplete and erroneous reporting in water quality can produce misleading results, 26 which would then propagate to modeled estimates. Our results are based on suspected cholera incidence estimates from 2010 to 2016; as newer and perhaps better data become available, updates to these analyses should be performed.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Additionally, these estimates represented an average over time, which may have attenuated the apparent associations between measures. Previous work has suggested that incomplete and erroneous reporting in water quality can produce misleading results, 26 which would then propagate to modeled estimates.…”
Section: Discussionmentioning
confidence: 99%